Avaliação dos processos de gestão do conhecimento e inovação no setor de serviços: desenvolvimento de modelo e estudo de caso - Aragão Neto, Raymundo Moniz de (2008)
The service sector represents the main share in the Brazilian Gross Domestic Product, and the economic development of countries depends upon the efficiency of their organizations to provide services to people. Knowledge management and innovation are recognized as survival factors for enterprises, and criteria for their evaluation allow managers to act in a more effective manner to their improvement. From the identification of several aspects related to knowledge management and innovation, as well as other services specificities, a model which generates a set of indicators for one specific enterprise is developed. A case study shows the results from model application in an Energy Service Company ESCO. Additional recommendations are also presented.